PENGARUH MINUMAN YOGURT TERHADAP pH SALIVA SISWA SEKOLAH DASAR - Siti Sulastri (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLETHE EFFECT OF DRINKING YOGURT ON THE pH SALIVA OF ELEMENTARY SCHOOL STUDENTSABSTRACT Saliva is one of the factors that influence the process of caries because saliva always wet the teeth so that affect the environment in the oral cavity. Saliva works not only to help in chewing food but also serves as a protector. Children often consume foods and beverages containing carbohydrates, so the caries-causing bacteria in the oral cavity will produce acids that cause demineralization. Among feeding periods, saliva will work to neutralize acids and help the process of remineralization. Consuming yogurt can be an effort to prevent caries in children. Yogurt contains calcium, which, if maintained longer in saliva, is expected to help with remineralization. The purpose of this study was to determine the effect of drinking yogurt on saliva pH. This research is a true experiment with the design of Pre and Post Test With Control Group Design. The population is all students of class I to class V Elementary School of Argomulyo, Sedayu, Bantul. The sample in this study amounted to 100 students by using random sampling technique. The data analysis used is the Wilcoxon test. The results showed that before drinking yogurt pH saliva 6,80, after drinking yogurt pH saliva 7.44 with difference 0,64. Drinking yogurt can increase saliva pH so that there is the influence of drinking yogurt to pH saliva of Elementary School Student of Argomulyo Sedayu Bantul Yogyakarta (p = 0,005). Keywords : yogurt, saliva pH___________________________________________________________*) Jurusan Keperawatan Gigi Poltekkes Kemenkes Yogyakarta * : sitislstr7@gmail.com